Effect of oil reactivity on salinity profile design during alkaline-surfactant-polymer flooding. (15th October 2019) - Han, Xu; Kurnia, Ivan; Chen, Zhao; Yu, Jianjia; Zhang, Guoyin
Abstract: This study focused on the influence of oil reactivity (ability to react with alkali to generate in situ surfactants) on salinity profile design during alkaline/surfactant/polymer (ASP) flooding. Two surrogate oils with different total acid number (TAN) were used. After determination of optimum salinity via phase behavior tests, 3 ASP corefloods with I-III-I, II-III-I (negative salinity gradient), and I-II-I salinity profiles were performed for each oil. ASP flooding was applied as a post-polymer enhanced oil recovery (EOR) method in this study. The results demonstrated: (1) for both low TAN oil and high TAN oil, when I-III-I salinity profile was employed, incremental oil recovery was less than 20% original oil in place (OOIP); (2) when negative salinity gradient was applied, high oil recovery from 33.5% to 38.5% OOIP was achieved over polymer flooding, resulting in cumulative recovery over 95% in spite of oil reactivity; (3) distinct trends were observed for corefloods with I-II-I salinity profile. For low TAN oil, an incremental recovery of only 20% OOIP was attained; by contrast, for high TAN oil, the incremental recovery was as high as 35.1%, which could be attributed to the generation of a large amount of in situ soaps that had lower optimum salinity compared to the added surfactants; and (4) ASP flooding proved to be an effective EOR approach to significantly reduce residual oil after polymer flooding if appropriate salinity profile was adopted. This study provides some guidance on salinity profile design when ASP flooding is considered for oils with different reactivity.